LyF-1, a transcriptional regulator that interacts with a novel class of promoters for lymphocyte-specific genes. - Lo, K (1991)
We have studied transcriptional control of the murine terminal deoxynucleotidyltransferase (TdT) gene, which is activated specifically in immature B and T lymphocytes. This analysis has led to the identification and purification of a 50-kDa sequence-specific DNA-binding protein, LyF-1, that interacts with the approximate consensus sequence PyPyTGGGAGPu and is enriched in cells at most stages of B- and T-cell differentiation. LyF-1 binds tightly to an element in the TdT promoter that we show is required for transcription in lymphocytes. LyF-1 also interacts with an element in the immunoglobulin mu enhancer, called microB, that was recently shown to be important for lymphocyte-specific enhancer activity. Moreover, LyF-1 binds to the promoters for the lymphocyte-specific genes lambda 5, VpreB, and lck, all of which we speculate have additional features in common with the TdT promoter. Thus, LyF-1 may be a general transcriptional activator for genes whose expression is restricted to the B- and/or T-lymphocyte lineages.